Energy from the Desert: Feasibility of Very Large Scale Photovoltaic Power Generation (VLS-PV) Systems - 黒川, 浩助 (Routledge, 2007)
The world's deserts are sufficiently large that, in theory, covering a fraction of their landmass with PV systems could generate many times the current primary global energy supply. This Energy from the Desert volume examines and evaluates the potential of very large scale photovoltaic power generation (VLS-PV) systems. Following from the success of the first book on the subject, the authors present practical case studies of both virtual and real projects based on selected regions (including the Mediterranean, the Middle East, the Gobi Desert and Western Australia) and their specific socio-economic dynamics, and argue that VLS-PV systems in desert areas will be readily available in the near future. As the essential companion to the previous International Energy Agency (IEA) volume it reiterates and develops key concepts introduced by the original study and provides firm practical recommendations to achieve long-term targets for policy-makers and investors.